Effects of climate and land management changes on conservation : of mediterranean cork oak woodlands and their bird communities - Correia, Ricardo (2015)
Tese de doutoramento (co-tutela), Biologia (Biologia da Conservação), Faculdade de Ciências da Universidade de Lisboa, University of East Anglia, School of Environmental Sciences, 2014